Adult life expectancy trends in the era of antiretroviral treatment in rural Uganda (1991–2012). (28th January 2016) - Asiki, Gershim; Reniers, Georges; Newton, Robert; Baisley, Kathy; Nakiyingi-Miiro, Jessica; Slaymaker, Emma; Kasamba, Ivan; Seeley, Janet; Todd, Jim; Kaleebu, Pontiano; Kamali, Anatoli
Abstract : Objective: To estimate the impact of antiretroviral therapy (ART) on population-wide adult life expectancy. Study design: A population-based open cohort study with repeated HIV status measurements and registration of vital events in Southwestern Uganda (1991–2012). Methods: Nonparametric survival analysis techniques are used for estimating trends in the adult life expectancy of the general population (aged 15 and above), the adult life expectancy by HIV status, and the adult life expectancy deficit. The life expectancy deficit is estimated as the difference between overall life expectancy and life expectancy of the HIV-negative population. All estimates are disaggregated by sex. Results: Between 1991–1993 and 2009–2012, population-wide adult life expectancy increased from 39.3 [95% confidence interval (CI): 35.9–42.8] to 56.1 years (95% CI: 54.0–58.5) in women, and from 38.6 (95% CI: 35.4–42.1) to 51.4 years (95% CI: 49.2–53.7) in men. Most of the adult life expectancy gains coincide with the introduction of ART in 2004; as evidenced by an increase in the adult life expectancy of people living with HIV between 2000–2002 and 2009–2012 of 22.9 and 20.0 years for women and men, respectively. Over the whole period of observation, the adult life expectancy deficit associated with HIV decreased from 16.1 (95% CI: 12.7–19.8) to 6.0 years (95% CI: 4.1–7.8) among women, and from 16.0 (95% CI: 12.1–19.9) to 2.8 years (95% CI: 1.2–4.6) among men. Conclusion: Population-wide life expectancy increased substantially, largely driven by reductions in HIV-related mortality. Women have gained more adult life years than men since the introduction of ART, but the burden of HIV in terms of the life years lost is still larger for women than it is for men. Abstract : Supplemental Digital Content is available in the text